Research on oscillation characteristics of wind farm sending system based on participation factor - Peng, Qiu; Jingen, Song; Qian, Chen; Wei, Zhou; Bingyu, Xiong; Aihong, Tang (Frontiers in Energy Research, 2022)
The MMC-HVDC transmission system of wind farm has a very broad application prospect, but is gradually a major concern that the system is prone to broadband oscillation. And the mechanism of oscillation remains to be clarified. In this paper, based on the basic principle of eigenvalue analysis, the theoretical calculation equation of quantitative evaluation index of participation factor is deduced. The small signal model of MMC-HVDC transmission system for a wind farm is established. Combining with the case of 200 wind turbines connected to the grid, the eigenvalue analysis method is used to obtain the dominant oscillation mode of the system. Participation factors of 11 oscillation modes of the system are calculated to further analyze the relationship between the oscillation modes and the state variables in the MMC-HVDC transmission system of wind farms. And the correlation between the participation factors of each oscillation mode, wind farm and the MMC system is investigated, which lays a foundation for the formulation of broadband oscillation suppression strategies.